Progress on lipase immobilization technology in edible oil and fat modifications - Ng, Lin Cieh; Mokhtar, Mohd Noriznan; Samsu Baharuddin, Azhari; P. Mohammed, Mohd Afandi; Wakisaka, Minato (Taylor & Francis Inc., 2023)
Lipase has been used extensively in the industrial sector for edible fats and oils processing. However, its industrial scale application is often hampered by limitations such as low stability and poor reusability. A countermeasure taken is lipase immobilization which is a technique to confine enzyme molecules within a fixed space while maintaining catalytic activity. This usually enhances lipase stability and allows its reusability together with other advantages like simple product separation and better design options for the bioreactor. Meanwhile, lipase immobilization often involves high cost and thus making them less attractive for certain industrial applications (e.g., monoglyceride and diglyceride production, vitamin C esters synthesis) compared to chemical catalysts. Their lower activity compared to free lipase and chemical catalysts is also a challenge that needs to be overcome. Therefore, this paper will discuss the important characteristics of lipase, trending materials and protocols used in lipase immobilization, and current applications of immobilized lipase in edible oil and fat industries. This is to provide a thorough understanding of lipase immobilization technology in edible oil and fat modifications so that the strategy for its application can be more appropriately designed for optimized industrial benefits.